Interpretation of the Maslahah-Based Principle as the Protection of Female Prisoners in the Criminal Justice System - Moh. Riziq; Choirul Anwar (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
Female prisoners face multidimensional vulnerabilities within a criminal justice system that predominantly reflects androcentric perspectives. Gender-specific needs, including reproductive health, psychological trauma, and motherhood, are often neglected, leading to systemic injustices. This study proposes the maslahah principle of Islamic law as a philosophical and normative foundation for strengthening the protection of female prisoners. The research aims to examine interpretations of maslahah relevant to addressing the specific vulnerabilities of female prisoners and to formulate a model for its application within criminal justice policies. This study employs a juridical-normative methodology supported by conceptual and philosophical approaches. The findings indicate that the maslahah principle can be operationalized through both substantive and structural dimensions. Substantively, it requires legal reforms that ensure the protection of reproductive rights and promote alternatives to detention for women. Structurally, it necessitates the establishment of women’s protection units, the training of gender-sensitive legal and correctional officials, and the transformation of legal culture through the internalization of values of justice and dignity for women. The study concludes that the protection of female prisoners constitutes an essential interest (ḍarūriyyāt) under the framework of maqāṣid al-sharī‘ah. By integrating Islamic legal principles with justice-oriented and gender-responsive policies, this research contributes an integrative and practical model for criminal justice reform aimed at enhancing gender responsiveness.